PENGARUH DOPING Al TERHADAP TiO2 SEBANGAI PENDEGRADASI LIMBAH TEKSTIL METYELENE BLUE - Julianti Lestari; Helga Dwi Fahyuan; Ngatijo Ngatijo (Prodi Fisika FST UNJA, 2018)
[Title : Effect Of Thin Layer Thickness TiO2/Al In Photocatalisles As A Metyelene Blending Textile Waste Blending] Research on the effect of TiO2/Al thin film thickness has been made with spin coating technique at a rotational speed of 1500 rpm for 20 seconds and 30 seconds. TiO2/Al thin layer was tested by Scanning Electron Microscopy (SEM) to see thickness and morphology. The resulting thickness is 1, 300 μm for a 20 second rotation time and a thin layer with a 30 second rotation time of 4.841 μm thickness. Furthermore, photocatalysts were tested for the MB analysis of MB textile waste and from a 100 ppm factory exposed in the sun for 3 hours. The results of absorbance waste after photocatalyst using UV-Vis obtained the greatest degradation value of 94.17% for MB MB of synthesis and 15.11% in MB from factory waste with TiO2 Al 4% thin film. Keywords:Doping, Degradation Value, Photocatalyst.